2008
DOI: 10.1007/s11999-008-0306-4
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Transfusion after Predonation of Blood for Elective Spine Surgery

Abstract: The literature suggests preoperative autologous blood donation in total joint arthroplasty is associated with increased overall transfusion rates compared with nondonation and is not cost-effective for all patients. We asked whether the amount of intraoperative blood loss and blood replacement differs between autologous donors and nondonors in elective spine surgery and whether the rates of allogeneic blood transfusions differ between the two groups; we then determined the cost of wasted predonated units. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
0
23
0
2
Order By: Relevance
“…The types of surgery vary and the levels to be operated differ for each case. For invasive surgeries such as fusion surgery and scoliosis surgery, the management to prevent allogenic transfusion has been examined (Behrman and Keim 1992;Chanda et al 2002;Brookfield et al 2008;Gause et al 2008;Savvidou et al 2009). However, for less invasive surgery such as decompression surgery, postoperative anemia has not been evaluated in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The types of surgery vary and the levels to be operated differ for each case. For invasive surgeries such as fusion surgery and scoliosis surgery, the management to prevent allogenic transfusion has been examined (Behrman and Keim 1992;Chanda et al 2002;Brookfield et al 2008;Gause et al 2008;Savvidou et al 2009). However, for less invasive surgery such as decompression surgery, postoperative anemia has not been evaluated in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have discussed the efficacy of intraoperative cell saver blood autotransfusion to prevent allogenic transfusion (Behrman and Keim 1992;Chanda et al 2002;Brookfield et al 2008;Gause et al 2008;Savvidou et al 2009). However, these reports did not compare intraoperative and postoperative bleeding volume.…”
Section: Discussionmentioning
confidence: 99%
“…A nonrandomized study has even showed increased blood loss in the cell-saver group [20]. Preoperative autologous blood donation has had mixed reports in the literature [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…19 Allogenic transfusion also increase the risk of infectious disease such as hepatitis B and C, HIV and nvCJD. 19 Predonation has several limitation in major spinal surgery such as difficulty of predicting which patients require blood tranfusion, 20,21 the high potential for wastage (up to 40% discarded autologous blood products), 20 a high level of communication across a variety of specialties necessary for successful implementation, and its inavailability in emergency surgeries. 4 With the exception of the estimated blood volume, the baseline demographic variables between the PD and non-PD groups were similar.…”
Section: Estimated Blood Volumementioning
confidence: 99%
“…20 Similarly, Kennedy et al examined elective posterior lumbar spine surgery in adult patients and found PD induced preoperative anemia. 7 The authors found preoperative Hct in patients who pre-donated was significantly lower (39.8 ± 4.5 vs 41.6 ± 4.6, p<0.001).…”
Section: Estimated Blood Volumementioning
confidence: 99%